A Large Impact of Cooking Organic Aerosol (COA) on Particle Hygroscopicity and CCN Activity in Urban Atmosphere. Issue 8 (15th April 2021) - Liu, Jieyao; Zhang, Fang; Xu, Weiqi; Chen, Lu; Ren, Jingye; Jiang, Sihui; Sun, Yele; Li, Zhanqing
Abstract: Cooking organic aerosol (COA) constitutes a considerable proportion of fine particles in populated area, while there is a lack of understanding on its impact on climate. Using a data set from field observations in Beijing, we characterize the variations of COA in fine particulate matter (PM) and its effect on aerosols hygroscopicity and cloud condensation nuclei (CCN) activity. The observed mass concentrations of COA from two campaigns of winter 2016 and summer 2017 were 5.5 ± 5.6 µg m −3 and 1.9 ± 2.1 µg m −3, respectively, corresponding to mass fraction of COA to PM1 and total OA of 8% ± 9% and 17% ± 13% in winter, 10% ± 9% and 19% ± 13% in summer. The strong COA sources are evidenced by apparent peak values in mass concentrations at lunch and dinner times. With increase of volume fraction of COA from ∼10% during noncooking time to ∼40% during dinner time, hygroscopic parameter of OA ( κ org ) is decreased from ∼0.21 to ∼0.06 (corresponding to a decrease of overall hygroscopic parameter of aerosols, κ, from ∼0.25 to ∼0.20), showing a critical role of COA in altering aerosols hygroscopicity. Further evaluation shows that the decrease in aerosols hygroscopicity caused by COA will reduce its CCN activity significantly (characterized by critical supersaturation, S c, increasing from ∼0.25%–0.5% to ∼0.4%–0.7%). The current circumstance, which presents no apparent downward trends of COA in Beijing during last decades but much greater levels of COA in China than those in other regions around the world, suggests the great significance to account for the effect of COA on regional climate in models. Key Points: The strong cooking organic aerosol (COA) sources are evidenced by two apparent peaks at lunch time and dinner time in the diurnal cycles COA plays a critical role in altering aerosols hygroscopicity in populated urban atmosphere The decrease of water uptake capacity of aerosols caused by COA will reduce the aerosol cloud condensation nuclei (CCN) activity greatly